Experiences of infected health care team during first wave of COVID-19 at Hilal-e-Ahmer Hospital, Faisalabad - Sumera Ehsan; Nuzhat; Ayesha Ayub; Tehseen Aslam (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: COVID-19 has caused a very deep and intense effect on all persons irrespective of age and gender. It was especially a challenging fight for health professionals as they were dealing it from many aspects. All the infected health workers were facing many emotional and mental stresses, and at the same time, they were supposed to provide error free services at the hospital. To explore the experiences of infected Health Care Providers during COVID-19 pandemic.METHODOLOGY:  The interview based qualitative descriptive research was conducted at Hilal-e Ahmar hospital Faisalabad, Pakistan. To get an in-depth idea about different experiences of the professionals, 15 Semi structured interviews were conducted during the first wave of COVID-19 pandemic in Pakistan. Convenient sampling was done by inviting all the infected members for the interviews. Purposive sampling was done, and a total of 15 interviews were conducted till the data was saturated. Participants gave their convenient time keeping in mind their easy duty days for the study, and they were interviewed in their offices.  Interviews were transcribed, rechecked, and analyzed. Thematic analysis was done with narrations.RESULTS:5 broader themes were generated with sub-themes. The themes were 1) Diagnosis of disease, 2) Disease impacts, 3) Social reaction, 4) Combating techniques for isolation period and, 5) Dilemmas during the quarantine period. The participants were diagnosed by PCR technique, and the diagnosis was associated with extreme feelings of denial, depression, anxiety, fear of the future and uncertainty. Most of the participants faced negative responses from society and experienced a social boycott.CONCLUSION: The first wave of COVID-19 was a period of extreme stress and anxiety, especially for the health care providers working as the first line of defense against the disease. They not only suffer from the physiological effects of the disease but faced mental trauma and social stigmatization. Electronic media had a negative effect on the thought process of people.